The EFFECT OF OIL PALM SAP TAPPING AT THE PITH AND 50 CM FROM THE PITH ON THE CHARACTERISTICS OF PRODUCED BACTERIAL CELLULOSE - Tyrta Wahidani; Wardatul Husna Irham (RADJA PUBLIKA, 2026)
This study aims to utilize oil palm sap as a fermentation medium for bacterial cellulose production using Acetobacter xylinum bacteria. The study used a non-factorial Completely Randomized Design (CRD) consisting of two treatments, namely sap tapping from the apical meristem and sap tapping 50 cm from the apical meristem. Parameters observed included membrane thickness, dry weight, weight after distilled water immersion, absorption capacity, and tensile strength of bacterial cellulose membranes. The results showed that sap tapped from the apical meristem produced the highest membrane thickness of 15.8 mm compared to 11.7 mm for sap tapped 50 cm from the apical meristem. ANOVA analysis showed that the tapping treatment significantly affected membrane thickness and weight after distilled water immersion, but had no significant effect on dry weight and absorption capacity of bacterial cellulose. The highest absorption capacity was obtained in the apical meristem treatment at 3.68 g/g, while the 50 cm treatment showed 3.58 g/g. Tensile strength analysis showed that the 50 cm treatment had a higher max stress value of 17.138 MPa compared to 15.919 MPa in the apical meristem treatment, while the apical meristem treatment showed a higher elongation value of 4.110 mm. Based on the results, differences in oil palm sap tapping locations affected the physical and mechanical characteristics of the bacterial cellulose produced.